A gene for autosomal dominant hearing impairment (DFNA14) maps to a region on chromosome 4p16.3 that does not overlap the DFNA6 locus. Issue 7 (1st July 1999) - Van Camp, Guy; Kunst, Henricus; Flothmann, Kris; McGuirt, Wyman; Wauters, Jan; Marres, Henri; Verstreken, Margriet; Bespalova, Irina N; Burmeister, Margit; Van de Heyning, Paul H; Smith, Richard J H; Willems, Patrick J; et al.
Abstract : Non-syndromic hearing impairment is one of the most heterogeneous hereditary conditions, with more than 40 reported gene localisations. We have identified a large Dutch family with autosomal dominant non-syndromic sensorineural hearing impairment. In most patients, the onset of hearing impairment is in the first or second decade of life, with a slow decline in the following decades, which stops short of profound deafness. The hearing loss is bilateral, symmetrical, and only affects low and mid frequencies up to 2000 Hz. In view of the phenotypic similarities of this family with an American family that has been linked to chromosome 4p16.3 (DFNA6), we investigated linkage to the DFNA6 region. Lod score calculations confirmed linkage to this region with two point lod scores above 6. However, as haplotype analysis indicated that the genetic defect in this family is located in a 5.6 cM candidate region that does not overlap the DFNA6 region, the new locus has been named DFNA14.